Determinant of Difficulty in Purchasing Decisions for Local Coffee Brands: Testing Knowledge of Product Class as Moderator - Refius Pradipta Setyanto; Kuswoyo Kuswoyo (Media Ekonomi dan Manajemen, 2021)
Coffee is one of the leading commodities in the plantation sub-sector in Indonesia because it has good market opportunities both locally and globally. The purpose of this research was to find out how the effect of perceived product similarity, product choices overload in the market toward decisions making difficulty, and knowledge of product classes as moderating variable. Data were collected using Google Forms and a self-administered questionnaire. Respondents in this study were 300 coffee consumers which were drawn using the purposive sampling method. Moderated regression was used to analyze this study.Â  The results showed that perceived product similarity influences product choices overload positively and decision-making difficulties negatively. Choice overload had an insignificant effect on decision-making difficulties, and product class knowledge moderates the effect of perceived product similarity on decision-making difficulty.Â  These findings provide insight into the importance of the brand as a distinguishing identity from other products.